Oral changes and their implications in pediatric patients with Down Syndrome (Research, Society and Development, 2024)
Down Syndrome (DS) is caused by trisomy of chromosome 21, resulting in various physical and mental anomalies. Although the etiology of DS is not fully understood, advanced maternal age is a significant risk factor. The objective of this article is to present an investigation of oral changes and their possible implications in pediatric patients with DS, seeking to elucidate the specific characteristics of these patients. Data collection was conducted using the PubMed, Scielo, and Lilacs databases with the keywords: Down Syndrome, Oral Health, and Pediatric Dentistry. The search was refined using the boolean operator "OR" and considered articles from the last five years (2018 to 2023) in both national and international literature. After applying the methodological criteria, 12 articles were selected as the corpus for analysis. The studies revealed that the most prevalent oral alterations in children with DS include delayed tooth eruption, dental anomalies, increased predisposition to periodontal diseases and cavities, as well as difficulties in chewing, speech, and swallowing. These findings highlight the importance of early diagnosis and multiprofessional care, including dental interventions, to improve the quality of life for these children.